2020
DOI: 10.7717/peerj.9286
|View full text |Cite
|
Sign up to set email alerts
|

Association of FKBP5 polymorphisms with patient susceptibility to coronary artery disease comorbid with depression

Abstract: Background Coronary artery disease (CAD) and depression cause great burden to society and frequently co-occur. The exact mechanisms of this comorbidity are unclear. FK506-binding protein 51 (FKBP51) is correlated with cardiovascular disease and depression. The aim of this study was to determine the role of the seven single nucleotide polymorphisms (SNPs) of FKBP5 that code FKBP51, namely, rs1360780 (C>T), rs2817032 (T>C), rs2817035 (G>A), rs9296158 (G>A), rs9470079 (G>A), rs471390… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
10
2
Order By: Relevance
“…Similarly, Piechaczek et al reported that no main genetic effects of the five SNPs (rs3800373, rs9296158, rs1360780, rs9470080, and rs4713916) on depression were found [ 13 ]; Lou et al reported that rs7757037 of FKBP5 was associated with depression in Chinese systemic lupus erythematosus patients [ 40 ] in dominant model. However, this finding was inconsistent with a study among patients with coronary artery disease, indicating rs2817032 was not associated with depressive symptoms among those patients [ 41 ]. The diversity of populations, which might result in various gene sensitivity, may explain the discrepancy of genotype models, while this study focused on Chinese adolescents.…”
Section: Discussioncontrasting
confidence: 73%
“…Similarly, Piechaczek et al reported that no main genetic effects of the five SNPs (rs3800373, rs9296158, rs1360780, rs9470080, and rs4713916) on depression were found [ 13 ]; Lou et al reported that rs7757037 of FKBP5 was associated with depression in Chinese systemic lupus erythematosus patients [ 40 ] in dominant model. However, this finding was inconsistent with a study among patients with coronary artery disease, indicating rs2817032 was not associated with depressive symptoms among those patients [ 41 ]. The diversity of populations, which might result in various gene sensitivity, may explain the discrepancy of genotype models, while this study focused on Chinese adolescents.…”
Section: Discussioncontrasting
confidence: 73%
“…Similarly, Piechaczek et al reported that no main genetic effects of the ve SNPs (rs3800373, rs9296158, rs1360780, rs9470080, and rs4713916) on depression were found [14]; Lou et al reported that rs7757037 of FKBP5 was associated with depression in Chinese systemic lupus erythematosus patients [34] in dominant model. However, this nding was inconsistent with a study among patients with coronary artery disease, indicating rs2817032 was not associated with depressive symptoms among those patients [35]. The diversity of populations, which might result in various gene sensitivity, may explain the discrepancy of genotype models, while this study focused on Chinese adolescents.…”
Section: Discussioncontrasting
confidence: 69%
“…MAF of above all SNP were verified through 1000 Genomes CHB ( https://www.internationalgenome.org/ ), setting up cutoff MAF > 0.05. Among them, the SNPs rs2817035 and rs4713902 of the FKBP5 gene were reported as linked to risk for coronary artery disease [ 24 ]. A study of interindividual response differences to inhaled corticosteroids in patients with chronic obstructive pulmonary disease showed that rs4713916 is associated with sensitivity/resistance to corticosteroids [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, there is a distal enhancer located 65 kb downstream of the transcription start site in the fifth intron of the FKBP5 gene, and a study showed that FKBP5 expression is regulated by an interaction between the AR and this enhancer; specifically, AR selectively recruits cAMP response element-binding protein to this enhancer [ 22 ]. Moreover, it is notable that previous studies have shown that FKBP5 is highly expressed in muscle and adipose tissue, and human FKBP5 is associated with type 2 diabetes(T2D) and with markers for both insulin resistance and obesity [ 23 , 24 ]. Given that PCOS patients show symptoms like endocrine disorders, metabolic disorders, and obesity, we were interested in exploring potential relationships between FKBP5 and androgens in the context of PCOS etiology.…”
Section: Introductionmentioning
confidence: 99%